ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN MANAJEMEN DALAM PENYUSUNAN LAPORAN KEUANGAN KOPERASI DI KECAMATAN KEDIRI - Putu Diah Asrida; Ida Ayu Intan Maharini (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
This study aims to analyze the effect of education level, work experience, and training on management skills in the preparation of cooperative financial reports in Kediri sub-district in 2020. The research carried out is included in the type of causal associative research. The number of cooperatives that can be identified in Kediri District is 108 cooperatives. The sampling technique in this research is cluster sampling, which is an area sampling technique used to determine the sample if the object to be studied or the data source is very broad. The results showed that the variable level of education, work experience and training had a significant effect on management ability as evidenced by the F-count value of 20.824 which is greater than the F-table value of 3.187 with a sig value of 0.000 <0.05; The results of the coefficient of determination using the Adjusted R Square method state that the level of education, work experience and training has a significant effect on management ability in the preparation of cooperative financial statements with a value of 53.8% while the remaining 46.2% is influenced by other factors that are not included in the Research Model. There is a significant influence between the level of education, work experience and training on management skills in the preparation of cooperative financial reports in Kediri 2020